2017
DOI: 10.1016/j.molmet.2017.06.020
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as stress regulators in pancreatic beta cells and diabetes

Abstract: BackgroundMicroRNAs have emerged as important regulatory non-coding RNAs that tune cellular responses to physiological perturbations and disease conditions. An increasing body of literature underlines the important roles of miRNA function in pancreatic β-cells in response to metabolic, genetic and inflammatory stress. Lessons from genetic loss- and gain-of-function studies have implicated several highly expressed and evolutionary conserved miRNAs in stress signal modulation, resolution and buffering, thereby f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
126
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(129 citation statements)
references
References 126 publications
(166 reference statements)
3
126
0
Order By: Relevance
“…We found that miR-874-3p overexpression, similar to Nupr1 silencing, improved erection duration in DMED rats. 42 Moreover, miRNAs are also involved in cardiovascular complications arising from diabetes, 43 especially microcirculation dysfunctions. 40 Although miR-874-3p has not previously been implicated in diabetes, many other miRNAs are involved in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…We found that miR-874-3p overexpression, similar to Nupr1 silencing, improved erection duration in DMED rats. 42 Moreover, miRNAs are also involved in cardiovascular complications arising from diabetes, 43 especially microcirculation dysfunctions. 40 Although miR-874-3p has not previously been implicated in diabetes, many other miRNAs are involved in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, genetic deletion of miR‐200 family also confers positive effect on β‐cells but this is seen only during metabolic stress conditions such as when the pancreatic islets are under oxidative and ER stress . Taken together, these highly expressed miRNAs can both have positive and negative influence on the pancreatic β‐cell and their interplay may be highly important especially during metabolic stress …”
Section: The Involvement Of Islet Mirnas In T2dmentioning
confidence: 99%
“…It is obvious that the expression of mir‐375 is not significantly different in islets from non‐diabetic (ND) versus T2D donors (Figure A), whereas miR‐130a showed differential expression (Figure B). A list of abundant miRNAs, and another of differentially expressed miRNAs in human T2D or in mouse animal models were summarized in a recent review by LaPierre and Stoffel . Comparing the lists, it becomes obvious that there is large discordance, and that diabetes seldom associates with differential expression of the more abundant miRNAs, like miR‐375.…”
Section: The Involvement Of Islet Mirnas In T2dmentioning
confidence: 99%
See 2 more Smart Citations